Comperasion Analysis Of Piano Chairs Secondary Packaging At Pt. Chitose International Tbk - Sihombing, Tulus Martua; Adriant, Irayanti; Alviani, Riga (International Journal Labs, 2023)
PT. Chitose International is an industrial company operating in the furniture sector which is one of the manufacturers of piano chairs. In the distribution of these products to Japan, there were 5% defects in the packaging within a year. However, the company has a defect tolerance standard of only around 4%, this causes the author to want to make suggestions regarding the addition of plastic wrapping packaging to reduce packaging defects. This research uses the Monte Carlo simulation method with the simulation assumption of a reduction in defects of 2%, 5% and 8%. After carrying out a simulation of reducing defects by 2% in 1 year, cardboard damage can be reduced from 1,248 to 1,229 cardboard boxes, thereby saving Rp. 15,797,593. A simulation of reducing defects by 5% in 1 year can reduce cardboard damage from 1,230 to 1,169, thereby saving Rp. 38,758,762. A simulation of reducing defects by 8% in 1 year can reduce cardboard damage from 1,258 to 1,158, thereby saving Rp. 63,419,700.